Analysing Tesla’s $0 Marketing Strategy - Agarwal, Varsha (International Journal For Multidisciplinary Research, 2022)
Tesla, an American automobile company founded in 2003, has made serious efforts to create an altogether new driving experience and make electric cars the new normal. Despite being one of the first companies in the EV space, Tesla has been against advertising since its inception and hence is popularly recognised for its “$0 marketing strategy”. The research involves identifying the reason why Tesla adopts this unique marketing strategy and the potential impacts it may have in the future. Using a survey questionnaire and a deep Market Share analysis, the study identifies that the company has been able to create brand awareness to a great extent and holds a prominent position in the market. In conclusion, the investigation reflects how the marketing strategy has been one of the most crucial decisions in contributing to their growth and success. However, it may also be the reason for a future downfall considering the vast majority of entrants are looking towards scraping off Tesla’s throne to become the market leader.
ISME
Keywords: Marketing strategy; Market share analysis; Brand recognition and reputation; Market leader; Social media platforms